Evaluation of curriculum aspects of early childhood education programme in Nigeria (2011)
This paper examined the curriculum contents of early childhood education programme in Nigeria. Areas focused on were the curriculum contents, implementation strategies, materials put in place for implementing the curriculum and transition rate of Nigeria children from nursery classes to primary school. Issues that centred on discrepancies between curriculum recommendation and level of implementation were looked into. The paper also considered it necessary to shed light on the key concepts used in this study such as evaluation, curriculum, as well as early childhood education programme. Classroom Interaction Instrument (CII], interview schedules, documentary analysis and observation technique were used to generate information. Two hundred and fifty early teachers and 35 head teachers provided information needed for the study. Data analysis involved the use of qualitative method. The result revealed that learning is integrated across the development needs, however, with less emphasis on learning experiences (without recognizing differences in individual children's learning styles), prior experiences and different development rates. The curriculum implementers are expected to help as much as possible, ensure that children’s individual differences are considered during teaching-learning processes. Material provision should be central to early childhood classroom activities. Further, the use of play and not lecture method should be the prevailing teaching strategy used.